Studi Perbandingan Persepsi Stigma Teroris Antara Mahasiswa Laki-Laki Dan Mahasiswa Perempuan di Universitas Riau - Permatasari, Dwi Puspa; Hambali, Hambali; Primahardani, Indra (Jurnal Kewarganegaraan, 2022)
AbstractThis study aims to describe a comparative study of perceptions of terrorist stigma between male and female students at the University of Riau. How the terrorism and bombing cases that occurred in Indonesia were masterminded by certain religious groups using certain symbols and attributes, giving rise to a negative stigma perspective between male and female students at the University of Riau. The method used in this study is a quantitative method with a descriptive approach. The data collection technique in this research is a questionnaire consisting of five indicators and 19 questions. The data analysis technique in this study was using the Independent Sample T-test with the SPSS version 25 program. After testing the normality of the data with normal data results and testing the homogeneity of variance with homogeneous data results, then hypothesis testing can then be carried out. The results of the hypothesis test are 1,000 and the value of 1,000 > 0.05 (2-tailed < 0.05), then Ha is rejected and Ho is accepted. Based on the results of the study, it can be concluded that there is no difference in perceptions of terrorist stigma between male and female students at the University of Riau.--------------------AbstrakPenelitian bertujuan untuk mendeskripsikan studi perbandingan persepsi stigma teroris antara mahasiswa laki-laki dan mahasiswa perempuan di Universitas Riau. Bagaimana kasus terorisme dan pengeboman yang terjadi di Indonesia didalangi oleh sekelompok oknum agama tertentu dengan menggunakan simbol serta atribut tertentu, sehingga menimbulkan perspektif stigma negatif antara mahasiswa laki-laki dan perempuan di Universitas Riau. Metode yang digunakan dalam penelitian ini adalah metode Kuantitatif dengan pendekatan Deskriptif. Teknik pengumpulan data pada penelitian ini yaitu kuesioner/angket yang terdiri dari lima indikator dan 19 pertanyaan. Teknik analisis data dalam penelitian ini adalah menggunakan uji analisis Independent Sample T-test dengan program SPSS versi 25. Setelah melakukan uji normalitas data dengan hasil data normal dan uji homogenitas varian dengan hasil data homogen, maka selanjutnya dapat dilakukan pengujian hipotesis. Hasil uji hipotesis adalah 1,000 dan nilai 1,000 > 0.05 (2-tailed < 0.05), maka Ha ditolak dan Ho diterima. Berdasarkan hasil penelitian maka dapat disimpulkan bahwa tidak terdapat perbedaan persepsi stigma teroris antara mahasiswa laki-laki dan mahasiswa perempuan di Universitas Riau.